Características neuroendocrinas del trauma temprano y su relación con el bullying (2017)
The aim of this article is to review the theoretical basis of neurobiological and neuroendocrine mechanisms that develop early trauma, which can be generators cognitive and emotional vulnerability in subjects exposed to environments with characteristics of child abuse; furthermore, it seeks to identify the relationship between early vulnerability cognitive expressed and affectively with relationships concerning profiles of child victims of bullying in early childhood and propose an explanatory framework for the development of profiles of vulnerability or resilience from the role that school as a protective factor for modifying the expression of genes in children and adolescents in vulnerable conditions. © 2017 Fundacion para la difusion neurologica en Ecuador - FUNDINE. All Rights Reserved.